2003
DOI: 10.1046/j.0004-8666.2003.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mixed mullerian tumour of the ovary: Prognostic factor and response of adjuvant platinum‐based chemotherapy

Abstract: Malignant mixed mullerian tumour of the ovary is a rare and aggressive gynaecological tumour. The current study indicates that patient age was a significant prognostic factor for survival and surgical cytoreduction combined with platinum-based chemotherapy is the most effective management regimen identified to date to treat MMMT of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…10 However, we found that age was not associated with a poorer prognosis by the log-rank test (Table S1, Supplemental Digital Content 1, http://links.lww.com/IGC/A198), which is consistent with the findings reported by Rutledge et al, 11 who also found that age did not affect survival. It is reasonable to assume that early-stage disease may lead to a better prognosis; however, to the best of our knowledge, no studies to date have been able to demonstrate that stage is a prognostic factor using multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…10 However, we found that age was not associated with a poorer prognosis by the log-rank test (Table S1, Supplemental Digital Content 1, http://links.lww.com/IGC/A198), which is consistent with the findings reported by Rutledge et al, 11 who also found that age did not affect survival. It is reasonable to assume that early-stage disease may lead to a better prognosis; however, to the best of our knowledge, no studies to date have been able to demonstrate that stage is a prognostic factor using multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Other clinical prognostic factors associated with poor outcome have been described in the literature, including older age and suboptimal surgical resection [4,21]. Optimal cytoreduction is associated with a survival benefit in women with advanced stage epithelial ovarian cancer [22], however, the reported benefit in patients with OCS is more variable ( Table 2).…”
Section: Prognostic Factorsmentioning
confidence: 96%
“…Women >65 years of age have been reported as showing a significantly lower survival rate than younger women, although optimal debulking and the presence of a sarcomatous component were not significant prognostic factors for survival [27]. Cox multivariate analysis, including age, tumor stage, amount of residual disease, histology and type of adjuvant therapy, showed that tumor stage and adjuvant platinum-based chemotherapy in combination with paclitaxel or ifosfamide were predictors of a positive outcome [18].…”
Section: Discussionmentioning
confidence: 99%